Tourism and leisure: Current issues and perspectives of development - Pechlaner, Harald; Smeral, E. (2015)
The Festschrift in honor of Prof. Dr. Peter Keller, president of the International Association of Scientific Experts in Tourism (AIEST) since 1994, represents a wide range of tourism research as well as the current state of the ongoing debates in tourism as a scientific research field. The aim is to cover multiple topics and trends in travelling and to discuss future development possibilities in the leisure industry.